PENGGUNAAN METODE EKSPERIMEN PADA PEMBELAJARAN MATERI SIFAT BAHAN DAN KEGUNAANNYA TERHADAP HASIL DAN RESPON BELAJAR SISWA KELAS IV MIN TUNGKOB ACEH BESAR - Wati Oviana; Maulidar Maulidar (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2013)
The research on the use of experimental methods in learning characteristics of material and its usefulness toward students’ achievements and learning responses of Level 4 primary school students of MIN Tungkob Aceh Besar aims to determine students’ learning outcomes and responses toward the use of the method. This study uses experimental research. The data collection techniques were using test and distributing questionnaire to the students. The samples in this experimental study were students of class IV3 totaling 34 people as the experimental class and the class IV4 totaling 31 people as the control class. The data, which is the students’ learning outcomes collected from pretest and posttest, were analyzed using t-test formula. The data from the students’ questionnaire responses were analyzed using percentage formula.The result was that the students’ learning outcomes from the experimental class and the control class showed significant differences. Students’ responses toward the use of experimental methods in learning material characteristics and its usefulness were also very positive, where the students are very excited and interested in learning to use the experimental method in the study of material characteristics and its usefulness.